Using Stardew Valley to Enhance EFL Reading Skills in Vocational Education - Muhammad Syafiq; Titi Rokhayati; Sri Widodo (Research, Training and Philanthropy Institution Natural Aceh, 2026)
Reading comprehension remains a major challenge for Indonesian vocational students learning English as a Foreign Language (EFL), partly because conventional instruction often fails to promote engagement. This study investigated the effectiveness of Stardew Valley, a commercial farming simulation game, as an authentic digital learning medium to improve EFL reading comprehension. A pre-experimental one-group pretest–posttest design was employed involving 36 tenth-grade vocational students. Participants completed a pretest, engaged in a structured 50-minute gameplay session emphasizing dialogue, quest instructions, and contextual reading tasks, and then completed a posttest. Reading comprehension was measured using a validated 25-item multiple-choice test. The findings revealed that the mean score increased from 55.00 to 66.94. A paired-samples t-test indicated a statistically significant improvement, t(35) = 9.580, p < 0.001, with a large practical effect (Cohen’s d = 1.597). These findings demonstrate that integrating commercial digital games into EFL instruction can effectively enhance reading comprehension while fostering greater learner engagement in vocational education.